2012
DOI: 10.17705/1jais.00319
|View full text |Cite
|
Sign up to set email alerts
|

Examining Knowledge Management Enabled Performance for Hospital Professionals: A Dynamic Capability View and the Mediating Role of Process Capability

Abstract: Research ArticleIng-Long Wu National Chung Cheng University ilwu@mis.ccu.edu.tw Ya-Ping Hu

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
105
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(108 citation statements)
references
References 86 publications
2
105
0
1
Order By: Relevance
“…First, in knowledge management, two studies aimed to develop generalizeable theories (Teo and Men, 2008;Wu and Hu, 2012), whereas the other three papers examined the influence of unique Chinese socio-cultural factors on knowledge management in using IS. Specifically, Huang et al (2011) focused on the impact of trust, guanxi orientation and face, on employees' intentions to share knowledge in Chinese firms.…”
Section: Is Managementmentioning
confidence: 99%
“…First, in knowledge management, two studies aimed to develop generalizeable theories (Teo and Men, 2008;Wu and Hu, 2012), whereas the other three papers examined the influence of unique Chinese socio-cultural factors on knowledge management in using IS. Specifically, Huang et al (2011) focused on the impact of trust, guanxi orientation and face, on employees' intentions to share knowledge in Chinese firms.…”
Section: Is Managementmentioning
confidence: 99%
“…In general, organizational capability is defined as the ability to adapt ongoing changes in the business processes and functional activities of the firm [41], while it is also described as -an organization's ability to create value in a unique way by utilizing resources‖ [42] from the RBV perspective. From a dynamic capability perspective, two types of distinctive organizational capabilities -planned dynamic capability and improvisational capability -have been identified from the core business processes for boosting business value [40].…”
Section: The Elements Of Organizational Capabilitiesmentioning
confidence: 99%
“…Rhodes et al (2008) indicated that a good information system could help employees to implement knowledge transfer, and hence to avoid the loss of valuable work experience and expertise. Wu and Hu (2012) found from the study on hospitals that the interaction between knowledge assets and abilities, program abilities and performance would significantly affect the performance of implementing knowledge management. Chau et al (2011) learned that technical and cultural capabilities would affect the interrelationship of markets through innovative business processes.…”
Section: Relationship Between Knowledge Management Infrastructure Andmentioning
confidence: 99%